1995
DOI: 10.1074/jbc.270.9.4870
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Insulin Receptor Substrate-1 Protein

Abstract: Insulin receptor substrate-1 (IRS-1) is a major endogenous substrate of the insulin receptor. To study the interaction of the insulin receptor with IRS-1 in vitro, we expressed in Escherichia coli the amino acids 516-777 of human IRS-1 (hIRS-p30) covering five potential tyrosine phosphorylation sites within YXXM motifs. Kinetic data for tyrosine phosphorylation of hIRS-p30 by partially purified insulin receptor and insulin-like growth factor I receptor and by baculovirus-expressed insulin receptor kinase domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…To analyze whether the C‐terminal tyrosine phosphorylation has an influence on the catalytic properties of the IR kinase domain (IRKD), we have constructed a kinase mutant, in which the two tyrosine residues (Tyr 1316 and Tyr 1322 ) were replaced by phenylalanine (IRKD‐Y2F). In the present study, we have compared the enzymatic properties of the mutant kinase with the wild‐type enzyme IRKD, a widely used model for the IR [16–21]. Our data indicate that the phosphorylation of the C‐terminal tyrosine residues appears to be play a role in fine‐tuning of the kinase activity.…”
Section: Introductionmentioning
confidence: 91%
“…To analyze whether the C‐terminal tyrosine phosphorylation has an influence on the catalytic properties of the IR kinase domain (IRKD), we have constructed a kinase mutant, in which the two tyrosine residues (Tyr 1316 and Tyr 1322 ) were replaced by phenylalanine (IRKD‐Y2F). In the present study, we have compared the enzymatic properties of the mutant kinase with the wild‐type enzyme IRKD, a widely used model for the IR [16–21]. Our data indicate that the phosphorylation of the C‐terminal tyrosine residues appears to be play a role in fine‐tuning of the kinase activity.…”
Section: Introductionmentioning
confidence: 91%
“…Siemester et al (58) have reported that a 262-amino acid IRS-1 region comprising five tyrosine phosphorylation sites within YXXM motifs is an excellent substrate of the insulin receptor; and after this IRS-1 domain is tyrosine phosphorylated, it binds more tightly to the insulin receptor.…”
Section: F18mentioning
confidence: 99%
“…It is not clear which receptor and IRS-1 domains mediate this stable association, nor what role this stable association plays in IRS-1 phosphorylation in intact cells. However, a recent study has suggested that regions in the C-terminal half of IRS-1 may play a role in binding to the insulin receptor [16]. Studies with the two-hybrid system have identified a domain present in IRS-2 that may contribute to receptor-IRS-2 interactions [ 171.…”
mentioning
confidence: 99%